Host Immune Responses and Pathogenesis to Brucella spp. Infection - Oliveira, Sergio Costa; Giambartolomei, Guillermo (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Brucellosis, caused by the facultative intracellular bacteria Brucella species, is one the most prevalent zoonosis worldwide. • The articles described in this book report several aspects of host-Brucella interactions. • The findings described here will help to advance in the comprehension of bacterial pathogenesis and contribute to the future development of drugs or vaccines to control brucellosis.